Implementasi Social Media Optimization (SMO) Bagi Perusahaan Swasta di Jakarta - Putri, Citra Eka (Jurnal Pustaka Dianmas, 2022)
SMO (Social Media Optimization) is one of the methods used to increase online traffic targeted at social media activities. SMO is one way for SMM (Social Media Marketing) to attract visitors through social media activities. But unfortunately the management of social media by utilizing SMO is still not ideal among many social media managers, especially business owners in Indonesia. The purpose of this activity is to provide training for companies that focus on managing social media among private companies in Jakarta to be able to improve the optimization and performance of their social media. The material presented is related to how to optimize social media, create SMO strategies, focus on visuals on social media, optimize profiles, optimize content, optimize hashtags, create content production timelines, monitor social media performance, utilize social media insight metrics and optimize human resources by creating KPI managers. social media. The results of this training social media managers are able to understand how to optimize social media, be able to directly manage and create quality product content, understand and understand reading social media graphics, be able to make progress reports or insights on social media, and manage social media professionally able to create product content timelines on social media.